Foreword - Ian Goldman (The Evaluation Center at Western Michigan University, 2023)
This special edition of JMDE is a watershed for the International Evaluation Academy - the first science output, and on such an important topic. The collaboration with JMDE has been outstanding, and we would like to pay tribute to Michael Harnar, Bagele Chilisa, and Nicky Bowman for their dedicated work shepherding this edition. We hope this can be an important contribution to rethinking how evaluation can be fit for purpose in a world of polycrises, where the traditional Western growth models have led us to the brink of catastrophe. We need different ways of looking at the world, and learning from indigenous and decolonized approaches will be key in us garnering the wisdom to learn and transform how we use evaluation in the service of humanity and Nature, rather than for continued exploitation and despoilation. We hope this will be the first of many collaborations with the Journal. We wish you all fruitful reading and engagement.